Improving Learning Outcomes Benefits of Physical Activity with QR Code Movement Card Media in Students - Hidayat, Ropik; Mustafa, Annasari; Indarwati, Wiwik; Fauzi, M. Imam (Department of Physical Education, Sport, Health and Recreation, 2023)
Large-scale social restrictions brought on by the COVID-19 pandemic have changed learning in schools into learning at home. Students face challenges in the learning process, particularly in physical education classes, due to the inaccessibility of sports facilities and the absence of assistance, which increases the risk of injury and prevents students from comprehending the benefits of physical activity and how to perform movement tasks. The purpose of this research is to help students overcome their obstacles by using the Movement Card QR Code media as an independent study guide containing movement procedurals, movement classifications, movement benefits, and video demonstrations of movement steps. Two cycles of classroom action research based on the Kemmis and Taggart paradigms were used in this research. In the first cycle, cognitive domain classical completion was 70.58 % and psychomotor domain classical completion was 88.23%. The second cycle of classical completion is comprised of 91% cognitive and 94% psychomotor components. Conclusion: The employment of Movement Card QR Code media has a substantial impact on student learning outcomes. In addition, pupils were highly motivated to learn about the advantages of physical activity. By altering the context of the material to be provided, the Movement Card QR Code media can be utilized at the junior or senior high school level.